SKALA EMOTIONAL WELL BEING (EWB) BAGI MAHASISWA DI MASA PANDEMI COVID 19 - Rosalia Dewi Nawantara; Setya Adi Sancaya (Jurnal Bimbingan dan Konseling Borneo, 2021)
ABSTRACTEmotional Well Being (EWB) is an individual's positive feelings in living life including a sense of happiness and life satisfaction. The COVID-19 pandemic is an extraordinary event that has an impact on all lines of life. The education sector has not been spared the impact of the COVID-19 pandemic. The study from home appeal, which has been running for more than a year, continues to suppress the spread of Covid-19 cases. However, behind this policy, there are problems that arise regarding the emergence of several psychological problems experienced by students related to EWB. The purpose of this research is to develop an emotional well-being scale for students during the Covid 19 Pandemic. The approach and stages of research used in this study are Research Development. The EWB scale in this study has been tested by experts on guidance and counseling materials, as well as field tests to determine the acceptability of the scale in terms of scale validity and reliability. Keywords: Scale, Emotional Well Being, Students, Covid 19 Pandemic ABSTRAKEmotional Well Being (EWB) merupakan perasaan positif individu dalam menjalani kehidupan meliputi rasa bahagia dan kepuasan hidup. Pandemi covid 19 merupakan kejadian luar biasa yang berdampak bagi seluruh lini kehidupan. Pada bidang pendidikan juga tidak luput dari imbas pandemi Covid-19. Himbauan study from home yang sudah berjalan selama satu tahun lebih terus dilakukan demi menekan penyebaran kasus Covid-19. Akan tetapi, dibalik kebijakan tersebut terdapat permasalahan yang muncul tentang munculnya beberapa masalah psikologis yang dialami oleh peserta didik yang berkaitan dengan EWB. Tujuan penelitian ini adalah unuk mengembangkan skala emotional well being bagi mahasiswa di Masa Pandemi covid 19. Pendekatan dan tahapan penelitian yang digunakan dalam penelitian ini adalah Research Development. Skala EWB dalam penelitian ini telah dilakukan uji ahli materi bimbingan dan konseling, serta dilakukan uji lapangan untuk mengetahui keberterimaan skala dilihat dari segi validitas dan reliabilitas skala. Kata Kunci : Skala, Emotional Well Being, Mahasiswa, Pandemi Covid 19